Rekonstruksi Perlindungan Whistleblower Narkotika Berbasis Maqāṣid al-Sharī‘ah dalam Perspektif Negara Hukum - Dirwansyah Dirwansyah; Muhamad Harun; K.A. Bukhori (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study analyzes the legal protection for whistleblowers in narcotics criminal cases in Indonesia through the perspective of Islamic Constitutional Law (Siyāsah Shar‘iyyah) and the theory of maqāṣid al-sharī‘ah. As an extraordinary crime, narcotics require active public participation, yet whistleblowers often face significant legal and physical risks. This normative legal research uses a statutory and conceptual approach to evaluate Law No. 35 of 2009 on Narcotics, Law No. 31 of 2014 on Witness and Victim Protection, and the 1945 Constitution. The results indicate a normative vacuum and regulatory fragmentation that fail to provide absolute immunity for whistleblowers. From an Islamic perspective, protecting whistleblowers is a constitutional-theological obligation to safeguard the five essential elements (al-darūriyyāt al-khamsah), particularly hifẓ al-nafs (protection of life) and hifẓ al-‘aql (protection of intellect). This study proposes a legal reconstruction that integrates constitutional principles with maqāṣid al-sharī‘ah to ensure comprehensive protection and legal certainty for those reporting narcotics crimes.